Evaluation of the Antibacterial Activity and the Remineralizing Potentiality of Two Natural Extracts and Their Mixture (In Vitro Study) - Saleh, Reham; Nagi, Shaymaa; Elgamily, Hanaa; Hassan, Shahinaz; El-Hashemy, Hadeer; Zaazou, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aimed to assess the antibacterial activity against the cariogenic Streptococcus mutans (ATCC 25175) and the commensal Actinomyces viscous (1300 EMCCN) oral bacteria and to determine the remineralizing effect of the previously demineralized bovine enamel lesion of ginger extract, eggshell extract as well as their mixture. METHODS: The two different extracts; eggshell extract and ginger extract were prepared as well as their mixture in an equal volume. Their antibacterial activity against S. mutans and A. viscous was assessed by well diffusion test and clear zones diameters measurement (mm). Chlorhexidine and Dimethyl sulfoxide solution were utilized as positive and negative control, respectively. Thirty-six anterior bovine teeth were subjected to artificial caries pH cycling regimen including alternate demineralization and remineralization for 5 days. Then they were randomly divided into three groups (G) (n = 12): G1: Ginger, G2: Eggshell, and G3: Mixture. Specimens of each group were separately immersed in 50 ml of the tested extract for 12 h seven successive days. Vickers Microhardness and Energy Dispersive X-ray (EDX) Analysis were assessed at baseline, after demineralization and remineralization. RESULTS: Both extracts had antibacterial effect against the profile growth of S. mutants. However, the mixture showed the highest statistically significant mean inhibition zone diameters (mm), followed by ginger and eggshell extracts with no statistically significant difference between them. Regarding the remineralizing efficacy; G1:(Ginger) group showed the highest statistically significant mean microhardness followed by G3:(Mixture) group, then eggshell treated specimens; which showed the least statistically significant mean microhardness values. Regarding EDIX analysis results, a statistically significant increase in F (wt%) after remineralization in both eggshell and ginger treated specimens. CONCLUSION: Ginger as well as mixture extracts not only have antibacterial effect against cariogenic bacteria but also have a strong remineralizing ability of demineralized enamel.